2008
DOI: 10.1002/hec.1414
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social value of health‐care interventions: a stated preference discrete choice experiment

Abstract: SUMMARYMuch of the literature on distributive preferences covers specific considerations in isolation, and recent reviews have suggested that research is required to inform on the relative importance of various key considerations. Responding to this research recommendation, we explore the distributive preferences of the general public using a set of generic social value judgments. We report on a discrete choice experiment (DCE) survey, using face-to-face interviews, in a sample of the general population (n 5 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 57 publications
7
109
1
Order By: Relevance
“…Moving onto respondents' occupation, we find significant heterogeneity in preferences. In Hungary, respondents 6 Purely equitable and purely efficient interventions are those where all equity attributes are set to one (with all efficiency attributes to zero) and those where all efficiency attributes are set to one (with all equity attributes to zero), respectively. 7 Results are available from the authors upon request.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving onto respondents' occupation, we find significant heterogeneity in preferences. In Hungary, respondents 6 Purely equitable and purely efficient interventions are those where all equity attributes are set to one (with all efficiency attributes to zero) and those where all efficiency attributes are set to one (with all equity attributes to zero), respectively. 7 Results are available from the authors upon request.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of rational and transparent approaches to priority setting, decisions are partly made based on ad-hoc priority settings [6][7][8][9]. With the preferences of decision makers playing an important role in decisions, several studies have attempted to elicit policy makers' preferences in recent years [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Following consumer choice theory (Lancaster 1966(Lancaster , 1971, and drawing on stated-preference methodology (as applied by Green and Gerard 2009), three scenarios were used to elicit preferences from samples of the general population. There is a genuine justification for including the public in priority setting within health and social care, given their role in funding the system and their first-hand experience of the various health care programs.…”
Section: General Population Sample-focus Groups and Face-to-face Surveymentioning
confidence: 99%
“…For instance, in many studies, the general population is willing to sacrifice some amount of health gain to support patients of a lower health status [8,9]. In other studies, however, health improvements and value for money were considered to be more important than the severity of disease or the existence of alternative therapy [10,11]. Regarding age, Baker et al [12] found that the public prefers to save the young compared with the old.…”
Section: Introductionmentioning
confidence: 97%